2022
DOI: 10.1186/s12915-022-01282-7
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and endostyle development in cyclostomes provides new insights into the evolutionary history of vertebrates

Abstract: Background The endostyle is an epithelial exocrine gland found in non-vertebrate chordates (amphioxi and tunicates) and the larvae of modern lampreys. It is generally considered to be an evolutionary precursor of the thyroid gland of vertebrates. Transformation of the endostyle into the thyroid gland during the metamorphosis of lampreys is thus deemed to be a recapitulation of a past event in vertebrate evolution. In 1906, Stockard reported that the thyroid gland in hagfish, the sister cyclosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The thyroid gland of the cyclostomes is not a glandular organ with clusters of follicles, but rather, the thyroid follicles are scattered throughout the pharynx (Kobayashi, 1987). Hagfish thyroid follicles are similar in early development and morphology to those of gnathostomes and represent the ancestral condition among extant vertebrates (Takagi et al, 2022). Electron microscopic analyses have revealed the presence of dense granules in the thyroid follicular epithelial cells of hagfishes, which are thought to contain iodine (Henderson & Gorbman, 1971; Fujita, 1975; Fujita & Shinkawa, 1975; Suzuki, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thyroid gland of the cyclostomes is not a glandular organ with clusters of follicles, but rather, the thyroid follicles are scattered throughout the pharynx (Kobayashi, 1987). Hagfish thyroid follicles are similar in early development and morphology to those of gnathostomes and represent the ancestral condition among extant vertebrates (Takagi et al, 2022). Electron microscopic analyses have revealed the presence of dense granules in the thyroid follicular epithelial cells of hagfishes, which are thought to contain iodine (Henderson & Gorbman, 1971; Fujita, 1975; Fujita & Shinkawa, 1975; Suzuki, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that some lamprey characteristics that had been regarded as ancestral to the cyclostomes, such as the larval-type oral apparatus (Miyashita et al, 2021) and the transformation of the larval endostyle into the thyroid after metamorphosis (Takagi et al, 2022), are in fact the derived state from the acquisition of the ammocoete larval stage. Lampreys and hagfish split around 470 to 390 million years ago (Kuraku & Kuratani, 2006), and their morphology subsequently diverged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lampreys, the thyroid gland takes on the function of an exocrine organ, known as an endostyle during the larval period. This was long considered to be an ancestral condition, but recently it has been suggested to be a secondary condition (Takagi et al, 2022). Although there is some difference in the arrangement of blood vessels, both lamprey and hagfish have the scattered distribution of thyroid follicles along the bifurcated ventral aorta (for lamprey, see Takagi et al, 2022).…”
Section: Thyroid Gland Of E Burgeri Represents the Common Form Of The...mentioning
confidence: 99%
“…The morphology of the hagfishes is regarded to be highly derived, including the degeneration of eyes because of adaptation to the deep sea (Dong & Allison, 2021; Gabbott et al, 2016), and many studies have instead used lampreys as a model for cyclostomes. However, recent studies have suggested that some lamprey characteristics that had been regarded as ancestral to the cyclostomes, such as the larval‐type oral apparatus (Miyashita et al, 2021) and the transformation of the larval endostyle into the thyroid after metamorphosis (Takagi et al, 2022), are in fact the derived state from the acquisition of the ammocoete larval stage (still, careful discussion is necessary; see Mallatt, 2023). Lampreys and hagfish split around 470–390 million years ago (Kuraku & Kuratani, 2006; also see Miyashita et al, 2019), and their morphology has highly diverged.…”
Section: Introductionmentioning
confidence: 99%